Fingerstick Glucose Monitoring in Veterans Affairs Nursing Home Residents with Diabetes Mellitus. Issue 2 (16th October 2020) - Jeon, Sun Y.; Shi, Ying; Lee, Alexandra K.; Hunt, Lauren; Lipska, Kasia; Boscardin, John; Lee, Sei
Abstract : BACKGROUND/OBJECTIVE: Guidelines recommend less intensive glycemic treatment and less frequent glucose monitoring for nursing home (NH) residents. However, little is known about the frequency of fingerstick (FS) glucose monitoring in this population. Our objective was to examine the frequency of FS glucose monitoring in Veterans Affairs (VA) NH residents with diabetes mellitus, type II (T2DM). DESIGN AND SETTING: National retrospective cohort study in 140 VA NHs. PARTICIPANTS: NH residents with T2DM and older than 65 years admitted to VA NHs between 2013 and 2015 following discharge from a VA hospital. MEASUREMENTS: NH residents were classified into five groups based on their highest hypoglycemia risk glucose‐lowering medication (GLM) each day: no GLMs; metformin only; sulfonylureas; long‐acting insulin; and any short‐acting insulin. Our outcome was a daily count of FS measurements. RESULTS: Among 17, 474 VA NH residents, mean age was 76 (standard deviation (SD) = 8) years and mean hemoglobin A1c was 7.6% (SD = 1.5%). On day 1 after NH admission, 49% of NH residents were on short‐acting insulin, decreasing slightly to 43% at day 90. Overall, NH residents had an average of 1.9 (95% confidence interval (CI) = 1.8–1.9) FS measurements on NH day 1, decreasing to 1.4 (95% CI = 1.3–1.4) by day 90. NH residents on short‐acting insulin had the most frequent FS measurements, with 3.0 measurements (95% CI = 2.9–3.0) on day 1, decreasing to 2.6 measurements (95% CI = 2.5–2.7) by day 90. Less frequent FS measurements were seen for NH residents receiving long‐acting insulin (2.1 (95% CI = 2.0–2.2) on day 1) and sulfonylureas (1.7 (95% CI = 1.5–1.8) on day 1). Even NH residents on metformin monotherapy had 1.1 (95% CI = 1.1–1.2) measurements on day 1, decreasing to 0.5 (95% CI = 0.4–0.6) measurements on day 90. CONCLUSION: Although guidelines recommend less frequent glucose monitoring for NH residents, we found that many VA NH residents receive frequent FS monitoring. Given the uncertain benefits and potential for substantial patient burdens and harms, our results suggest decreasing FS monitoring may be warranted for many low hypoglycemia risk NH residents.